Pengaruh Penataan Arsip Dan Kompetensi Petugas Arsip Terhadap Kualitas Pelayanan Di Sekretariat Direktorat Jenderal Pencegahan Dan Pengendalian Penyakit Kementerian Kesehatan - Luthfi Alaqram; Dwi Agustina (Jurnal Ilmu Administrasi Publik, 2023)
The Influence of Archive Management and Competence of Archive Officers on Service Quality at the Secretariat of the Directorate General of Disease Prevention and Control, Ministry of Health. The purpose of this study was to analyze how much influence Archive Management and Archive Officer Competence have on Service Quality, both partially and simultaneously. The population and sample in this study are all employees who handle archives totaling 35 people. The independent variables in this study are Archive Management (X1) and Archive Clerk (X2) while the dependent variable is Quality of Service (Y). Based on this study, the t test of the effect of Archive Arrangement (X1) on Service Quality (Y) with a sig value <0.05. The magnitude of the influence is 0.255 or 25.5%. While the influence of Archive Officer Competence (X2) on Service Quality (Y) with a sig value <0.05. The magnitude of the influence is 0.337 or 33.7%. Then the effect of Archive Arrangement (X1) and Archive Officer Competence (X2) simultaneously on Service Kutas (Y) is 0.463 or 46.3%.